EFFECT OF COOPERATIVE CAPITAL ON SUCCESS AT KSP-PS BQ ARAFAH MATANGKULI - Suci Fitriani; Suci Faiza; Chaera Maulida; Rozhatul Saufa; Cut Dara Aria Faradika (PT. Radja Intercontinental Publishing, 2023)
This study aims to examine the effect of cooperative capital on success in savings and loan cooperatives. This study uses data for 2020 and 2021 obtained from KSP-PS BQ ARAFAH Matangkuli. The results of the research partially show that capital in 2021 has a negative effect and has experienced a significant decrease in KSP-PS BQ ARAFAH Matangkuli income. Simultaneous research shows that the capital variable has a negative effect on income sourced from operating income (sales and purchase income, profit sharing income , and other income.